Differential Contribution of the Gata1 Gene Hematopoietic Enhancer to Erythroid Differentiation - Suzuki, Mikiko (American Society for Microbiology (ASM), 2009)
GATA1 is a key regulator of erythroid cell differentiation. To examine how Gata1 gene expression is regulated in a stage-specific manner, transgenic mouse lines expressing green fluorescent protein (GFP) reporter from the Gata1 locus in a bacterial artificial chromosome (G1BAC-GFP) were prepared. We found that the GFP reporter expression faithfully recapitulated Gata1 gene expression. Using GFP fluorescence in combination with hematopoietic surface markers, we established a purification protocol for two erythroid progenitor fractions, referred to as burst-forming units-erythroid cell-related erythroid progenitor (BREP) and CFU-erythroid cell-related erythroid progenitor (CREP) fractions. We examined the functions of the Gata1 gene hematopoietic enhancer (G1HE) and the highly conserved GATA box in the enhancer core. Both deletion of the G1HE and substitution mutation of the GATA box caused almost complete loss of GFP expression in the BREP fraction, but the CREP stage expression was suppressed only partially, indicating the critical contribution of the GATA box to the BREP stage expression of Gata1. Consistently, targeted deletion of G1HE from the chromosomal Gata1 locus provoked suppressed expression of the Gata1 gene in the BREP fraction, which led to aberrant accumulation of BREP stage hematopoietic progenitor cells. These results demonstrate the physiological significance of the dynamic regulation of Gata1 gene expression in a differentiation stage-specific manner.